Advagraf® with or without an induction therapy for de novo kidney-transplant recipients. (3rd June 2018) - Noble, Johan; Jouve, Thomas; Rostaing, Lionel; Malvezzi, Paolo
ABSTRACT: Introduction : Cornerstone immunosuppressive therapy currently relies on immediate-release tacrolimus, a calcineurin inhibitor (CNI) that is potentially nephrotoxic and is more diabetogenic than cyclosporine A. Two new formulations of tacrolimus have been launched: an extended-release formulation (Advagraf®/Astagraf XL®, Astellas company) and a long-lasting formulation (Envarsus®, Veloxis company). Area covered : Herein, we assess the efficacy of an extended-release formulation of tacrolimus (Advagraf®/Astagraf XL®) used in conjunction with or without an induction therapy (i.e., basiliximab) in de novo kidney-transplant recipients. To achieve this, we searched for suitable articles through PubMed. Expert commentary : Phases-III and -IV studies comparing Advagraf®/Astagraf XL® to Prograf® in association with mycophenolate mofetil (more than 2, 500 patients) have demonstrated overall similar results with regards to patient/graft survival, biopsy-proven acute-rejection rate, and renal function (p > 0.05). A randomized controlled study in maintenance kidney transplant patients has shown (using electronic monitoring) that, as compared to Prograf®, Advagraf® significantly improved adherence to medication. Other studies report that Advagraf®-treated patients receiving a mTOR-inhibitor agent (sirolimus or everolimus) instead of MMF: this was associated with good allograft outcome, and might also prevent late-onset cytomegalovirus infection. Advagraf®-based immunosuppression given to de novo kidney-transplant recipients, with or without an induction therapy, provided excellent results compared to Prograf®; it also increased patients' adherence to treatment.